11-8x=2(8-4x)-5

Simple and best practice solution for 11-8x=2(8-4x)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-8x=2(8-4x)-5 equation:


Simplifying
11 + -8x = 2(8 + -4x) + -5
11 + -8x = (8 * 2 + -4x * 2) + -5
11 + -8x = (16 + -8x) + -5

Reorder the terms:
11 + -8x = 16 + -5 + -8x

Combine like terms: 16 + -5 = 11
11 + -8x = 11 + -8x

Add '-11' to each side of the equation.
11 + -11 + -8x = 11 + -11 + -8x

Combine like terms: 11 + -11 = 0
0 + -8x = 11 + -11 + -8x
-8x = 11 + -11 + -8x

Combine like terms: 11 + -11 = 0
-8x = 0 + -8x
-8x = -8x

Add '8x' to each side of the equation.
-8x + 8x = -8x + 8x

Combine like terms: -8x + 8x = 0
0 = -8x + 8x

Combine like terms: -8x + 8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 32=25-7x | | (22B-9)-7(3B+1)=-4 | | 30-10y=10 | | 4/(1-((5-25x)/4)) | | 68=m-46 | | x+7overx-5=0 | | f(x)=-x^2+1.8x+14.4 | | 2(4-x)=x | | -2x-4x-12=6 | | 3j+-2j-11=7 | | -8x+2y=-6 | | -x-2x-7x-2=32 | | n^2+12n-49=-10 | | 5(2+x)=7x-20 | | (15x-9)=y | | 2x(2-x)=x | | 9n-32=24n-1 | | 0.32/0.56=8/x | | 8-8b=8(b-7) | | N+4-3=2 | | f(x)=-2x^2+4x-1 | | -4(5t-4)+7t=5t-7 | | 9(x-4)=37 | | 6(x-.333)=-2(x+23) | | 540-3x=360-2x | | 14x-(x-5)+8=13 | | 320=0.2(1.500+x) | | -(7-4k)=9 | | .9x+8.25=1.5(2+2x) | | 3y=-6x-21 | | -15+5=-2(x+7) | | 6(x-3)+2x=4(2x-1)-22 |

Equations solver categories